PELATIHAN PELAKSANAAN PERENCANAAN PEMBANGUNAN DI TINGKAT DUSUN DAN PENYUSUNAN DOKUMEN RPJM DESA KEPADA PERANGKAT DESA, BPD DAN TIM PENYUSUN RPJM DESA (Di Lingkungan Pemerintahan Desa Kulur) - Haris Fauzi; Asep Qustolani; R. Neny Kusumadewi (Universitas Majalengka, 2023)
Abstract The Village Medium-Term Development Plan (RPJMDes) is an elaboration of the vision and mission for the village in the welfare of village communities. The Government of Kulur Village, Majalengka sub-district, Majalengka Regency experienced problems in implementing planning meetings at the hamlet level as a reference for planning at the Village level. Other problems in preparing the RPJMDes were due to the unavailability of up-to-date village profile data and a lack of awareness of the importance of the planning document and the insufficient capacity of the tools villages in preparing the RPJMDes. This community service program aims to strengthen the capacity of the village government, BPD and the drafters of the Kulur Village RPJMDes through training in the implementation of development planning and training in preparing the Village RPJMDes. This program is carried out in the form of training and mentoring. The result of this activity is an increase in the understanding of village officials, the BPD and the RPJMDesa drafting team in carrying out planning at the hamlet level and also in preparing the RPJMDes. The target achievement of this activity is the realization of the independence of village officials, the BPD and the RPJMDesa drafting team in carrying out planning and preparing the RPJMDesa in the future. Keywords: village development plan; preparation of RPJMDesa. Abstrak Rencana Pembangunan Jangka Menengah Desa (RPJMDes) merupakan penjabaran visi dan misi kepada desa dalam mensejahterakan masyarakat desa. Pemerintah Desa Kulur kecamatan Majalengka, Kabupaten Majalengka mengalami permasalahan dalam pelaksanaan musyawarah perencanaan di tingkat dusun sebagai acuan untuk perencanaan di tingkat Desa, Permasalahan lainnya dalam penyusunan RPJMDes karena tidak tersedianya data profil desa terkini dan kurangnya kesadaran betapa pentingnya dokumen perencanaan tersebut dan kurang memadainya kemampuan perangkat desa dalam menyusun RPJMDes. Program pengabdian ini bertujuan untuk menguatkan kapasitas pemerintahan Desa, BPD dan Penyusun RPJMDesaKulur melalui pelatihan pelaksanaan perencanaan pembangunandan pelatihan penyusunan RPJMDes. Program ini dilaksanakan dalam bentuk pelatihan dan pendampingan. Hasil kegiatan ini berupa meningkatnya pemahaman perangkat desa, BPD dan Tim penyusun RPJMDesa dalam melaksanakan perencanaan di tingkat dusun dan juga penyusunan RPJMDes. Target capaian kegiatan ini adalah terwujudnya kemandirian perangkat desa, BPD dan Tim penyusun RPJMDesa dalam melaksanakan perencanaan dan menyusun RPJMDesa di masa yang akan datang. Kata Kunci:rencana pembangunan desa; penyusunan RPJMDesa.